NEK1 variants confer susceptibility to amyotrophic lateral sclerosis - Kenna, Kevin P; van Doormaal, Perry T C; Dekker, Annelot M; Ticozzi, Nicola; Kenna, Brendan J; Diekstra, Frank P; van Rheenen, Wouter; van Eijk, Kristel R; Jones, Ashley R; Keagle, Pamela; Shatunov, Aleksey; Sproviero, William; et al. (Nature genetics, 2016)
Jan Veldink and colleagues show that loss-of-function variants in NEK1 are associated with susceptibility to amyotrophic lateral sclerosis (ALS). In addition to finding an excess of rare loss-of-function NEK1 variants in ALS cases, they report a significant association between a specific NEK1 missense variant (p.Arg261His) and disease risk. To identify genetic factors contributing to amyotrophic lateral sclerosis (ALS), we conducted whole-exome analyses of 1,022 index familial ALS (FALS) cases and 7,315 controls. In a new screening strategy, we performed gene-burden analyses trained with established ALS genes and identified a significant association between loss-of-function (LOF) NEK1 variants and FALS risk. Independently, autozygosity mapping for an isolated community in the Netherlands identified a NEK1 p.Arg261His variant as a candidate risk factor. Replication analyses of sporadic ALS (SALS) cases and independent control cohorts confirmed significant disease association for both p.Arg261His (10,589 samples analyzed) and NEK1 LOF variants (3,362 samples analyzed). In total, we observed NEK1 risk variants in nearly 3% of ALS cases. NEK1 has been linked to several cellular functions, including cilia formation, DNA-damage response, microtubule stability, neuronal morphology and axonal polarity. Our results provide new and important insights into ALS etiopathogenesis and genetic etiology.